Rhizospheric microbial consortium of Lilium lancifolium Thunb. causes lily root rot under continuous cropping system - Dai, Liangliang; Singh, Sunil K.; Gong, Hao; Tang, Yuanyuan; Peng, Zhigang; Zhang, Jun; Wu, Dousheng; Zhang, Huiming; He, Danxia (Frontiers in Microbiology, 2022)
Lily (Lilium lancifolium Thunb) is a cash crop with long-term cultivation history in China. Root tissue from lily has been used as a valuable component of Chinese medicine. Continuous cropping is a conventional planting approach for lily, which leads to heavy root rot disease. However, it is not clear how continuous cropping cause lily root rot disease. In this study, we performed rhizosphere microbiome analysis and microbial protein function prediction of lily with continuous cropping from 3 geological soil. In order to explore the specific rhizosphere microbiota triggering lily root rot disease, lily was contrasted with maize grown in similar system which showed no disease development. Additionally, we conducted soil chemical elements detection. Interestingly, Pseudomonas and Streptomyces genus with pathogenic function are dominant in lily rhizosphere. Lower soil pH of lily compared to maize supports pathogenic bacteria accumulation in lily rhizosphere. Meanwhile, we discovered that Flavobacterium genus bacteria with predicted phosphate transport function specifically accumulated in maize rhizosphere. Our findings suggest that Pseudomonas and Streptomyces may result in continuous cropping-induced lily root rot disease and Flavobacterium could serve as a protector of maize from pathogenic bacteria attack.